Heritability estimates and genetic trends for performance test traits in Old Kladruber horses - Alexandra Novotná; Alena Svitáková; Jitka Schmidová (Acta Fytotechnica et Zootechnica, 2016)
The Old Kladruber horse is an important Czech genetic resource. The objectives of this paper were estimate coefficients heritability and determinate genetic trends for evaluated traits. The data set for evaluation was composed of edited records of performance test for stallion and mare in years 1995-2014. Each horse had three to five performance evaluations for the suite of traits. Together eight evaluated traits was assessed: rideability, overall Impression, walk, trot, Canter and driveability of carriage - dressage test and obstacle driving test. The statistical model included fixed effects for sex, age, year/place, variety, stud, classifier, permanent environment and additive genetic effect. The heritability estimates were in range from 0.06 to 0.23. Genetic trends were constant over the analysed period, annual genetic change were close to zero in all traits except type and gender expression and trot